From graduation to underemployment: tackling the structural imbalances in skill development and job creation / Low Choon Wei - Low, Choon Wei (UiTM Cawangan Johor, 2025)
Graduate underemployment is a critical issue affecting both developed and developing countries. Despite a significant rise in the number of graduates, the labour market faces a persistent mismatch between the qualifications of graduates and available job opportunities. This study investigates the trends, causes, and consequences of skill mismatch, focusing on the growing concern of overeducation. Despite the increasing number of graduates, the analysis reveals a widening gap between the number of graduates produced and the availability of skilled jobs. The Malaysian labour market has seen a shift in job creation, emphasising semi- skilled positions rather than high-skilled roles. As a result, graduates increasingly take on jobs that only partially utilise their qualifications, contributing to rising underemployment. The economic consequences of underemployment are significant, as graduates' skills remain underutilised in roles that fail to match their expertise. This mismatch not only reduces individual productivity but also limits overall economic growth. Socially, underemployed graduates may experience lower wages, job dissatisfaction, and a sense of unfulfillment, which can further exacerbate career stagnation. To address this issue, the gap between the growing number of graduates and the creation of skilled jobs must be closed. This study calls for a coordinated effort from the government, educational institutions, and industries to address these structural imbalances, ensuring that graduates are equipped with the skills needed for emerging job opportunities and contributing to sustainable economic development.